2021
DOI: 10.1101/2021.04.23.21256007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Park Use in U.S. Cities

Abstract: IntroductionThe COVID-19 pandemic focused attention on city parks as important public resources. However, it is unknown how city park use in 2020 compared to prior years and whether COVID-19 may have exacerbated racial/ethnic inequities in access. Moreover, traditional methods of measuring park use present major drawbacks.MethodsWe analyzed monthly mobility data derived from a large panel of smartphone devices, cross-referenced with a database of parks locations sourced from local agencies. We assessed park us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
15
1
1
Order By: Relevance
“…Our results showing a drop in urban park visitation during the pandemic mirror some studies documenting declines in urban park use over the same time period (Jay et al, 2021), but they appear to contradict other reports indicating a rise in park visits during COVID-19 (Day, 2020;Pregitzer et al, 2020;Venter et al, 2020). Such discrepancies might be explained in several ways.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Our results showing a drop in urban park visitation during the pandemic mirror some studies documenting declines in urban park use over the same time period (Jay et al, 2021), but they appear to contradict other reports indicating a rise in park visits during COVID-19 (Day, 2020;Pregitzer et al, 2020;Venter et al, 2020). Such discrepancies might be explained in several ways.…”
Section: Discussioncontrasting
confidence: 83%
“…Results also reflect disparities in park use and access to greenspace that have been observed in other countries during the pandemic (Burnett et al, 2021;Dushkova et al, 2021). In US-based studies, researchers found park visits during the pandemic decreased the most in areas where park availability was low (Curtis et al, 2021) and more residents were BIPOC (Jay et al, 2021). In places where park distribution and access is inequitable (i.e., socially vulnerable neighborhoods), alternative pathways to nature and outdoor recreation may be critical.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Under anything but the most extreme situations, outdoor walks and exercise at safe distances were not only allowed, but encouraged for sustaining physical, mental, and emotional health and well-being (Samuelsson et al, 2020;Slater et al, 2020). While research on overarching patterns of open space use during the pandemic is still emerging-the use of some natural areas, parks, forests, trails, and bike paths increased (Grima et al, 2020;Venter et al, 2020;Outdoor Industry Association and Naxion Research Consulting, 2021;Plitt et al, 2021 this issue), but this increase was moderated by park closings and occurred more often in white majority neighborhoods in cities (Jay et al, 2021). Certain spaces became overcrowded, and some were closed to public use during the peak of the pandemic.…”
Section: Introductionmentioning
confidence: 99%